An analysis of whether a working-age ward-based liaison psychiatry service requires the input of a liaison psychiatrist. (June 2017) - Guthrie, Elspeth A.; McMeekin, Aaron T.; Khan, Sylvia; Makin, Sally; Shaw, Ben; Longson, Damien
Abstract : Aims and method: This article presents a 12-month case series to determine the fraction of ward referrals of adults of working age who needed a liaison psychiatrist in a busy tertiary referral teaching hospital. Results: The service received 344 referrals resulting in 1259 face-to-face contacts. Depression accounted for the most face-to-face contacts. We deemed the involvement of a liaison psychiatrist necessary in 241 (70.1%) referrals, with medication management as the most common reason. Clinical implications: A substantial amount of liaison ward work involves the treatment and management of severe and complex mental health problems. Our analysis suggests that in the majority of cases the input of a liaison psychiatrist is required.